Political Communication Patterns through Social Media: A Case of an Indonesian Presidential Staff Twitter Account - Herdin Arie Saputra; Addin Khaerunnisa Juswil; Sanny Nofrima (CommIT (Communication and Information Technology) Journal, 2022)
Given the current technological developments, social media has become a necessity and a new tool that can complement services. Social media can influence the understanding of political communication and its impact on the public. Every element of society uses social media for various purposes, including the government. One who is quite active on Twitter and has repeatedly drawn controversy is the Presidential Chief of Staff, Retired General Moeldoko. The research investigates the pattern of political communication carried out by the Presidential Chief of Staff by focusing on his Twitter account and using the components of the effectiveness of political communication and media effects. The research applies a qualitative approach supported by the NVivo 12 Plus software. The data are collected using the NCapture for NVivo feature on the Presidential Chief of Staff’s Twitter account (@Dr Moeldoko). The results show that Moeldoko’s communication through Twitter is generally for the media or fellow government agencies. His communication is also a way to provide information about government programs. In addition, the research also finds that the alleged ineffectiveness in Twitter management is based on a decrease in account activity. It can be concluded that his pattern of communication is general, vertical, and not participatory.